Penggunaan Bahan Alam dalam Praktikum IPA dengan Keterbatasan Fasilitas Laboratorium untuk Memahami Pembelajaran Kontekstual Pada Peserta Didik Kelas V SD Inpres 34 Kabupaten Sorong - Arvianti, Leha Arya; Afifi, Erwinestri Hanidar Nur; Sudrimo, Sella Nofriska (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to determine the effect of using natural materials in science practicum activities amid limited laboratory facilities on understanding contextual learning among fifth-grade students at SD Inpres 34, Sorong Regency. Natural materials serve as an alternative medium for conducting science practicum due to the lack of proper laboratory equipment. The research was conducted from July 2024 to February 2025. A quantitative approach was used, employing a pre-experimental design with a one-group pretest-posttest model. The sample consisted of 22 students from SD Inpres 34, Sorong Regency. Data were collected through interviews and written tests in the form of a pretest and posttest. The results showed a significant difference in the average, maximum, and minimum scores before and after the treatment. The significance value was 0.000 < 0.05, indicating that H0 is rejected and H1 is accepted. It can thus be concluded that there is a significant difference in students' learning outcomes between the pretest and posttest, meaning that the use of natural materials in science practicum activities amid limited laboratory facilities has a positive effect on students’ understanding of contextual learning in fifth grade at SD Inpres 34, Sorong Regency.